STATUS KEWARGANEGARAAN GANDA DI INDONESIA - Femmie Cynthia (Jurnal Hukum Adigama, 2021)
Citizenship status is a right for everyone, it is stated in Article 28D Paragraph 4 of the 1945 Constitution which states that "everyone has the right to citizenship status." In Indonesia, the terms dual citizenship status (bipatride) and stateless status (apatride) are not known. However, there are exceptions regarding dual citizenship status, in Law Number 12 of 2006 concerning Citizenship it is regulated regarding limited dual citizenship status. The purpose of this paper is to find out how the regulation regarding dual citizenship status applies in Indonesia and the procedure for selecting citizenship status for children with dual citizenship in Indonesia. The research method used in this paper is a legal research method with data collection techniques through literature. The legal materials used are primary legal materials such as statutes, and secondary legal materials, namely books, doctrines and legal journals. Dual citizenship status is limited to children before the age of 18 and unmarried. After that, the child must choose one of the citizenships between Indonesian citizens or foreign citizens. The procedure for selecting Indonesian citizenship status is given no later than 3 years after turning 18 years old or already married by submitting an application along with the required documents.